Re-presenting Groote Schuur: Exploring phenomenological notions in architecture and landscape - Davids, Thaufir (School of Architecture, Planning and Geomatics, 2014)
This dissertation is about the re-presentation and appropriation of a contrived culturally manipulated landscape, the decaying and neglected site of the old Rhodes Zoo. It uses the phenomenological notions of boundary, horizon, transparency and memory to re-appropriate the site as a literal and metaphoric gateway, a park and an experience. While the project attempts to appropriate the landscape into a park, it does so neither by demarcating or restricting its surface, nor by gardening or loading it with anything superficially related to the programme or convention of an urban park. Instead, as an acknowledgement of the landscape’s inherent complexity, the project utilises familiar archetypes; the wall, steps, a pergola etc., to reconstitute the site through the act of describing. It is a strategy which depends on articulating differences between the familiar and unfamiliar, and making the variety of layers inherent in a site legible and resonant. The project attempts to execute architectural gestures which are complex or generative in a metaphoric sense but attainable with limited means. Their simplicity and familiarity gives each archetype a powerful tectonic, material and poetic presence. While each element strikes a specific relationship to the terrain, mapping the histories and topographic changes that have shaped the site. The richness and complexity of these devices comes from being essentially relevant to the site, as adjectives and maps describing its variations, measuring its slopes, noting its inflections and underlining its folds. While their complexity, like that of the landscape, means they cannot be described solely in terms of their function or syntax: strolling, respite or leisure. The project, always careful to stimulate the visitor’s attention and signal various strata rather than materialise them, engages the landscape’s phenomenal memory. Thanks to the project’s articulations, the landscape of the zoo site, although barely touched by the project, is transformed into a generative metaphor of its own substrate. The single univocal ground plane of the existing site is changed into an active terrain. Endowed with a certain depth through transparency and dignity as an instigator of the architectural process, the landscape is converted into a vehicle for the imagination of the site-seers who adventure there.